The Effect of Internal and External Factors of Banking to the SMEs Financing for BPRS in Indonesia - Jaenal Effendi; Nurkholis Yasmin (University of Merdeka Malang, 2017)
Small and Medium Enterprises had a strategic role in economic growth. One of the main problems faced by SMEs in Indonesia was the limited financial capital and access to finance. Islamic Rural Banks (BPRS) could play a significant role in providing financing for the development of the real sector through SMEs. This study aimed to analyze the influence of internal and external factors of banking to the SMEs financing for BPRS in Indonesia 2011-2016 periods using the Vector Error Correction Model (VECM) method. In the long-term of VECM estimation result showed that third-party funds, FDR, inflation, and IPI had a significant positive effect on SMEs financing, while BOPO, NPF, ERP, and BSBIS variables negatively affected SMEs financing. This study recommended the importance of increasing the proportion of SMEs financing in line with the increase in the number of third-party funds and putting more funds in the real sector than in the monetary sector.DOI: https://doi.org/10.26905/jkdp.v21i3.1221